ANALISIS PELANGGARAN MAKSIM PADA DIALOG TOKOH DALAM SERIAL VICTORIOUS - Bunga Alfadilla; Febrian Febrian (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze maxim violations in the teenage sitcom Victorious. The series features interactions that are often sarcastic, humorous, and spontaneous, making it relevant to examine from a pragmatic perspective. The study employs a descriptive qualitative method based on Grice’s Cooperative Principle Theory (1975), which includes the maxims of quantity, quality, relevance, and manner. The data were collected purposively from several episodes containing humorous elements and conversations that deviate from these principles. The analysis shows that all types of maxims are violated in the series, with relevance maxim violations being the most dominant. These violations function to create humor, strengthen character portrayal, and construct implicit meanings within the characters’ interactions. The findings indicate that maxim violations are not merely communicative deviations but also serve as effective linguistic strategies for generating humor and conversational dynamics.